Applied epidemiology theory to practice - Brownson, Ross C.; Petitti, Diana B. (New York ; Oxford : Oxford University Press, 2006)
Focusing on areas of public health practice in which the systematic application of epidemiologic methods can have a large and positive impact, this text applies traditional methods for determining disease aetiology to applications of public health.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Epidemiology -- Research -- Methodology